Crime in Teluk Intan. A socio-legal study / Shaharul Anuar Suhir - Suhir, Shaharul Anuar (Faculty of Law, 1986)
It is possible to point to certain characteristics which are generally found in acts which are crimes before we can define what crime is. The first characteristic of crimes is that they are acts which have a particularly harmful effect on the public and do more than interfere with merely private rights. Sir Carleton Allen writes: “crimes is crime because it consists in wrong-doing which directly and in serious degree threatens the security or well-being of society and because it is not safe to leave it redress- -able only by compensation of the party injured". This explains why acts have been made crimes either by judicial decision or by legislation and it does not necessarily accurately represent the present state of affairs. A crime may remain a long after it has ceased to be a threat to the security or well-being of society.